The age of American unreason - Jacoby, Susan 1945- (New York Pantheon Books, 2008)
Traces the current of anti-intellectualism from post-WWII to the present and argues that the nation's cult of unreason is both deadly and destructive.
The way we live now: just us folks -- The way we lived then: intellect and ignorance in a young nation -- Social pseudoscience in the morning of America's culture wars -- Reds, pinkos, fellow travelers -- Middlebrow culture from noon to twilight -- Blaming it on the sixties -- Legacies: youth culture and celebrity culture -- The new old-time religion -- Junk thought -- The culture of distraction -- Public life: defining dumbness downward -- Conclusion: cultural conservation.
Includes bibliographical references and index.
Donated by Atty. Mehol K. Sadain, UP Institute of Islamic Studies, 2018.
Keywords: Popular culture -- United States; Reason -- Social aspects -- United States; Social values -- United States; Social psychology -- United States; National characteristics, American; Mass media -- Social aspects -- United States